2016
DOI: 10.1017/s0954422416000044
|View full text |Cite
|
Sign up to set email alerts
|

How plausible is the use of dietaryn-3 PUFA in the adjuvant therapy of cancer?

Abstract: Considerable debate exists regarding the potential antineoplastic effect of dietary long-chain n-3 PUFA contained in fatty fishes. Since the majority of published data has proven that their intake does not induce toxic or carcinogenic effects in humans, their possible preventive use against cancer has been suggested. On the other hand, it is unlikely that they could be effective in cancer patients as a single therapy. Nevertheless, a considerable effort has been put forth in recent years to evaluate the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 153 publications
(218 reference statements)
0
23
0
Order By: Relevance
“…In our opinion, this topic deserves particular attention, particularly by the researchers who have been studying for decades the beneficial effects of ω-3 PUFAs in the prevention of CVD and cancer. 1,39,57,62,96,98,117 Even though this issue cannot be tackled exhaustively in just one paragraph, it is essential to outline some considerations.…”
Section: Mixed and Contrasting Outcomes Of Recent Human Studies And Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion, this topic deserves particular attention, particularly by the researchers who have been studying for decades the beneficial effects of ω-3 PUFAs in the prevention of CVD and cancer. 1,39,57,62,96,98,117 Even though this issue cannot be tackled exhaustively in just one paragraph, it is essential to outline some considerations.…”
Section: Mixed and Contrasting Outcomes Of Recent Human Studies And Tmentioning
confidence: 99%
“…This hypothesis is particularly interesting, since p-Akt represents a biomarker associated with poor prognosis in breast cancer, and used to evaluate the activity of the tyrosine kinase receptor signaling, often deregulated in breast cancer carcinogenesis. 57,61 A possible future ω-3 PUFA-containing nano-based approach for breast cancer may be suggested on the basis of the above analyzed remarkable results, obtained by both Alaarg et al 58 Since ω-3 PUFAs are known to potentially act as an adjuvant therapy to strengthen the activity of conventional chemotherapeutics or targeted drugs in the therapy of breast cancer, 57,62 it would be remarkable to develop nanoliposomal structures that are able to deliver simultaneously both ω-3 PUFAs and drugs with previously acknowledged activity in breast cancer. This liposomal combined approach could also be experimented in the clinical setting, since some liposomes are known to be safe and have already been clinically approved.…”
mentioning
confidence: 99%
“…However, growing epidemiological, experimental, and clinical evidence showing the beneficial effects of ω3 PUFA in several stages of CRC management represent a solid rationale for their exploitation in therapeutic combinatory strategies (28). The antineoplastic effects of ω3 PUFA have been studied for many years, and multiple biological mechanisms have been suggested to explain their inhibitory effects on cancer cell growth (29, 30).…”
Section: Dietary Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…As a matter of fact, it has been observed that the incorporation of LCn-3 PUFA in membranes alters the expressions of several signaling molecules residing there, and, in turn, modifies the activities of factors/pathways placed downwards [12,13]. Indeed, it has been suggested [14,15] that, thanks to their pleiotropic anticancer properties, LCn-3 PUFA could represent optimal candidates for adjuvant cancer therapy, in combination with conventional drugs as well as targeted therapies. As a matter of fact, some of the innovative anti-cancer therapies have failed due to their frequent and dangerous side effects, as well as to the multilevel cross stimulations occurring among the targets of these new biological agents.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility to combine more than one targeted agent has recently been suggested in order to suppress multiple signaling pathways and overcome resistance. The simultaneous treatment of mono-targeted drugs with multi-targeted dietary agents, such as LCn-3 PUFA, could also represent an interesting alternative option [14,17,18]. In particular, for their properties, these fatty acids do not induce any dangerous side effect at the doses generally used in patients, in addition to further improving the activities of the mono-targeted therapies.…”
Section: Introductionmentioning
confidence: 99%